New Emission Factors for Calculation of Ammonia Volatilization From European Livestock Manure Management Systems - Sommer, Sven G.; Webb, J.; Hutchings, Nicholas D. (Frontiers in Sustainable Food Systems, 2019)
The largest source of ammonia (NH3) emissions to the atmosphere is NH3 from agriculture, the majority of which arise from livestock manure. The NH3 emitted is a threat to human health through the formation of fine particles, causes eutrophication of natural ecosystems and is a loss of fertiliser nitrogen (N). The Convention on Long-Range Transboundary Air Pollution (CLRTP) and the European Union National Emission Ceilings Directive (NECD) sets limits for national NH3 emissions and require the reporting of annual emission inventories to demonstrate compliance. The EMEP/EEA Air Pollutant Emission Inventory Guidebook provides emission factors (EFs) to support inventory compilation. Here we report the development of revised NH3 EFs for livestock housing, manure storage, field-applied manure and excreta deposited during grazing. Data from 276 studies were used with more than 70% of these data from peer reviewed journals, the remaining being from conference proceedings and scientific reports. For most sources, the new EFs are the weighted means of the emissions reported. The empirical ALFAM model was used to develop EFs for field-applied slurry. The standard deviation of the EFs were substantial, due to the breadth of the categories of livestock and management systems and because of variations in manure management and climate. The data collected will be available at http://www.alfam.dk